Monopelopia mongpuense sp. n., a phytotelmata midge from sub–Himalayan region of India (Diptera: Chironomidae: Tanypodinae) - Paul, Nilotpol; Hazra, Niladri; Mazumdar, Abhijit (Zootaxa, 2014)
Immature and adult stages of Monopelopia mongpuense sp. n. from phytotelmata of Cedrus deodara (Lamb.) in Darjeeling are described along with biological notes. Key to the adult males of all species of the genus Monopelopia Fittkau is also presented. This genus is recorded for the first from Indian subcontinent.